Persepsi tokoh masyarakat dan peternak terhadap kinerja penyuluh dalam meningkatkan usaha peternakan sapi potong di Kecamatan Sangkub Kabupaten Bolaang Mongondow Utara - Umar, H; Lainawa, J; Lenzun, G D; Warow, Z M (Universitas Sam Ratulangi, 2021)
PERCEPTION OF COMMUNITY LEADERS AND FARMERS TOWARDS THE PERFORMANCE OF EXTENSION WORKERS IN IMPROVING BEEF CATTLE FARMING BUSINESS IN SANGKUB DISTRICT NORTH BOLAANG MONGONSOW This research was a descriptive research that is aim to know the perception of community leaders and breeders on the performance of extension workers. The selection of sample respondents was determined deliberately (Purposive) namely village officials, community leaders and farmers in the villages of Sangkub 1, Tombolango, Busisingo, Pangkusa and Sidodadi, as many as 30 respondents. Variable measurement is done by following the guidelines